Accurate resonant frequency of isosceles right‐angled triangular patch antenna. Issue 6 (27th March 2013) - Maity, Sudipta; Gupta, Bhaskar
Abstract Due to high quality factor compared to other regular well known shaped resonators, triangular resonators, and/or radiators attract much attention recently. The development of triangular geometry (except equilateral) is still in its early stages of research due to lack of proper theory. In this article, an isosceles right‐angled triangular microstrip antenna (TMA) is analyzed theoretically using well known cavity model. Internal field components are derived. An expression for predicting resonant frequency is obtained. Results are compared with published results to show the correctness of our theory. A simple expression for computing effective side length of isosceles right‐angled TMA is provided. A prototype is also fabricated to verify this theory. The error between theoretical and experimental resonant frequency is 0.0773%. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1306–1308, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27536